2005
DOI: 10.3171/ped.2005.102.3.0326
|View full text |Cite
|
Sign up to set email alerts
|

Progressive cranial nerve palsy following shunt placement in an isolated fourth ventricle

Abstract: Cranial nerve palsy is rarely seen after shunt placement in an isolated fourth ventricle. In the few reports of this complication, neuropathies are thought to be caused by catheter injury to the brainstem nuclei either during the initial cannulations or after shrinkage of the fourth ventricle. The authors treated a child who suffered from delayed, progressive palsies of the sixth, seventh, 10th, and 12th cranial nerves several weeks after undergoing ventriculoperitoneal shunt placement in the fourth ventricle.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 17 publications
(24 reference statements)
0
18
0
1
Order By: Relevance
“…10,12,24,25 The development of 6th and 7th cranial nerve palsies has been attributed to the catheter in the fourth ventricle; however, this appears unlikely. 12,24,25 The development of bulbar disturbance and tetraparesis is reminiscent of one pattern of presentation of Chiari I malformation. 26 Hydrocephalus is occasionally seen in Chari I and is relieved by decompression, which indicates that the obstruction is functional rather than due to scarring.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…10,12,24,25 The development of 6th and 7th cranial nerve palsies has been attributed to the catheter in the fourth ventricle; however, this appears unlikely. 12,24,25 The development of bulbar disturbance and tetraparesis is reminiscent of one pattern of presentation of Chiari I malformation. 26 Hydrocephalus is occasionally seen in Chari I and is relieved by decompression, which indicates that the obstruction is functional rather than due to scarring.…”
Section: Discussionmentioning
confidence: 96%
“…Pang et al described promising results in a patient similar to ours; his patient with isolated fourth ventricle and syringomyelia was initially treated with a fourth ventricular shunt. 12 This patient developed delayed progressive palsies of the 6th, 7th, 10th and 12th cranial nerves in the ensuing weeks. On MRI it appeared that the brain stem had shifted backward, possibly causing traction injury to the nerves.…”
Section: Discussionmentioning
confidence: 98%
“…Another case has been reported by Pang and coworkers. 7 They suggested that traction of the brain stem owing to continued CSF drainage may be the probable cause of multiple cranial nerves involvement. They treated their patient with release of arachnoid adhesions in the posterior fossa.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] Cranial nerves involvement is rare after shunt insertion in the fourth ventricle. 4,6,7 ''Direct stem injury'' at the time of operation, 6 ''touch'' of the surface of stem by catheter after decreased size of ventricle, 4 and ''traction'' of cranial nerves due to continuous cerebrospinal fluid (CSF) drainage 7 have been reported as the causes of this involvement.…”
mentioning
confidence: 99%
“…Most of the reports concern 6th and 7th nerve palsies, but 5th, 10th and 12th cranial nerve palsies have also been described 1 6 7 11–13. These complications, however, have been described mostly in children already having a VP shunt in the lateral ventricle since infancy.…”
Section: Introductionmentioning
confidence: 99%